Economic burden of alcohol-related cancers in the Republic of Korea. (1st December 2020) - Han, Minji; Tran, Binh Thang; Cho, Heeyoun; Oh, Jin-Kyoung
Highlights: Alcohol consumption is a major risk factor for cancer, a large burden of disease. Alcohol-attributable cancer accounted for 4.8 % of all cancer cases in Korea in 2016. The economic cost of alcohol-attributable cancer in 2016 was USD 33, 647 per capita. Policies to curb alcohol consumption may improve the costs related to cancer. Abstract: Background: Cancer is a major burden of disease and alcohol consumption is one of the major risk factors of cancer. This study aimed to estimate the economic burden of cancer types attributable to alcohol consumption in the Republic of Korea. Methods: This study estimates the direct and indirect costs of cancer types attributable to alcohol consumption by applying cost-of-illness methods using the human capital approach and prevalence-based estimates. Claims data from the National Health Insurance Service for 2011–2016 were used. Results: In Korea, there were 297, 304 alcohol consumption-related cancer cases, of which 14, 186 (4.8 %) were attributable to alcohol consumption in 2016. From 2011–2016, the socioeconomic burden of cancer attributable to alcohol consumption in Korea has increased steadily, even considering inflation adjustment. The total economic burden of cancer attributable to alcohol consumption in 2016 in Korea was approximately $476 million, of which $119 million were direct costs and $357 million were indirect costs. According to our analysis of annual cost per patient, the average costs were $37, 432 for men and $11, 930 for women. Conclusions: The economic burden of cancer types attributable to alcohol consumption in Korea is substantial and has increased between 2011 and 2016, mainly due to an increased number of patients.